May Day, Riley County - Garver, Andrew (Kansas State University, The Chapman Center for Rural Studies, 2012)
This study is about the small town of May Day, Riley County, Kansas. It includes interviews, early maps of the town site, and photographs of how the town stands right now.
Andrew Garver, “May Day, Riley County,” Chapman Center Research Collections, accessed October 26, 2020, https://ccrsresearchcollections.omeka.net/items/show/71.
Keywords: Tuttle Creek Dam; Belvue; District #28; May Day; Riley County; May Day Springs